Training on the Use of Batik Waste Processing Equipment to Enhance Productivity for the Wijirejo Pandak Bantul Batik Group - Amelia, Shinta; Evitasari, Rachma Tia; Rosyida, Miftahurrahma; Sabila, Liya Yusrina; Sabilihaq, Roby; Lestari, Betty Novia; Aini, Siti Nur (UKInstitute, 2024)
The batik industry is one that continues to develop over time. One of the ongoing concerns is the waste generated by the batik industry, particularly the dye content in batik dyes. Reactive dyes, if not processed properly, can have a very negative impact on the environment. They can pollute water sources, harm the surrounding environment, and even kill aquatic biota. Currently, liquid batik waste is stored in holding tanks and allowed to seep into the ground without further processing. Given the environmental impact of batik dyes, efforts must be made to minimize these effects before the waste is discharged into water bodies. A batik waste processing method currently under development is the Heterogeneous Fenton method. This method can degrade batik waste into compounds that are less harmful to the environment. The implementation of this service involves socialization and introduction of the program to the service partners, as well as training. This includes technology introduction, tool usage, and the transfer of scientific and technological knowledge to the service partners.